THE INFLUENCE OF ACCOUNTING INFORMATION SYSTEMS, GOOD CORPORATE GOVERNANCE, CORPORATE SOCIAL RESPONSIBILITY ON COMPANY PERFORMANCE MEDIATED BY ORGANIZATIONAL CULTURE - Yuyun Ardianti; Andry Priharta; Siti Hamidah Rustiana (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
This study aims to find out and examine whether accounting information systems, good corporate governance and corporate social responsibility affect company performance mediated by organizational culture. The research method used is quantitative with primary data in the form of distributing questionnaires to 4 and 5 star hotels in the West Nusa Tenggara region. The technique used to analyze the data is the Structural Equation model – partial least squares (SEM-PLS) method with SmartPLS 3. The results of this study indicate that the accounting information system has an insignificant positive effect on company performance, good corporate governance and corporate social responsibility have a positive and significant effect on company performance. Accounting information systems and good corporate governance have a positive and significant effect on organizational culture while corporate social responsibility has an insignificant positive effect on organizational culture. accounting information systems and good corporate governance have a positive and significant effect while corporate social responsibility has a positive and insignificant effect.